Efektivitas Experiential Marketing dan Media Penjualan Online pada Kepuasan Konsumen - Sholikhah Septiarti Khusnul Wardatus; Sudarno Sudarno; Khresna Bayu Sangka (Department of Economics Education, Universitas Sebelas Maret, 2021)
The purpose of this study was to determine the effectiveness of experiential marketing on consumer satisfaction, determine the effectiveness of online sales media on consumer satisfaction, and determine the effectiveness of experiential marketing and online sales media on consumer satisfaction. The research method is descriptive quantitative with the population used, namely consumers who have bought guppy fish in Solo Raya both offline and online, totaling 97 consumers. The sampling technique used in this research is purposive sampling. The results obtained in this study, reveal that: (a) There is an effectiveness between experiential marketing on consumer satisfaction, which can be seen from the acquisition of the value tcount > ttable, namely 5.503 > 1.989. (b) There is an effectiveness between online sales media on consumer satisfaction, it is known from the acquisition of tcount > ttable, which is 4,412 > 1,989. (c) There is an effectiveness between experiential marketing and online sales media on consumer satisfaction, it is known from the obtained Fcount value of 86,748 and Ftable obtained of 3,09. The hope for further researchers is to be able to improve the question instruments and indicators of each variable to find out in more detail the effectiveness of experiential marketing and online sales media on consumer satisfaction.